Impact of salinity on the kinetics of CO2 fixation by Spirulina platensis cultivated in semi-continuous photobioreactors - Ramirez-Perez, Javier Christian; Janes, Harry (Eclética Química, 2021)
In this research, the physiological response of the microalgae Spirulina platensis to salinity stress (1 and 100 g L-1 ) was investigated. Spirulina platensis and Spirulina platensis (adapted to high salt concentration) were operated at laboratory scale in a semi-continuous photobioreactors. The responses examined were within 0.5 to 10% CO2 concentration, temperatures from 10 to 40 oC, light intensities from 60 to 200 μmol m-2 s -1 and presented better results in terms of all kinetic parameters. The highest rate of CO2 biofixation for Spirulina platensis was 25.1 gCO2 m-3 h -1 , and the maximum specific growth (μmax) achieved was 0.44 d-1 - 0.67 d-1 at 2.5% CO2, 150 µmol m-2 s -1 at 25 oC. Corresponding determined values of Spirulina platensis adapted were 18.2 gCO2 m-3 h -1 , 0.31 d-1 - 0.58 d-1 at 2.5% CO2, 60 µmol s-1 m-2 and 28 oC. However, both microalgae exhibited experimental limiting growth factors, CO2 10%, 40 oC and 200 µmol m-2 s -1 , conditions under which photosynthetic CO2 biofixation may be inhibited and photoinhibition of photosynthesis may be enhanced by salinity. The efficiency of 2.5% CO2 removal by Spirulina platensis achieved 99%, whereas Spirulina platensis adapted to 96%, respectively. The kinetic parameters estimated for Spirulina platensis can be used to improve photobioreactor design for reducing of atmospheric carbon dioxide.